Relay Node Candidate Selection To Forwarding Emergency Message In Vehicular Ad Hoc Network - Johan Ericka (IC-ITECHS, 2014)
Sending emergency message in VANET environment has been studied lately to improve their effectivity. Due to the absence of network infrastucture and vehicle movement, every packet must be send to it’s destination by multi-hop. By using wireless network means that packet will be transmitted as broadcast. Every vehicle in the sources signal range will get the data packet and it has to rebroadcasted. Unfortunately some researchers has been studied that rebroadcast data packet at the same time will lead into broadcast storm program. There are many technique was developed to overcome broadcast storm but the most reseach using forwarder candidate to avoid broadcsat storm. This reseach will studied how to choose forwarder candidate among others node to rebroadcast emergency message efficiently without causing broadcast storm. Every node will calculate its delay time depend on some calculated value before rebroadcasting emergency message. If a node receive emergency message before it’s delay time’s up then it will cancel the delay countdown dan will not broadcast emergency message. There will be one broadcaster at a time dan the data packet will activate or deactivate delay countdown